Bilateral Facial Nerve Palsy following Head Injury: A Report of Two Uncommon Cases - Tanki, Humam Nisar; Syed, Shafeeq Alam; Bilal, Sobiya; Chisti, Nazish Aslam; Wani, Afzal; Sheikh, Javeid; Syed, Qawnain Kirmani; Bachh, Umar; Haque, Zia Ul (Indian Journal of Neurosurgery, 2020)
Bilateral facial nerve palsy (FNP) following head injury without any brain parenchymal injury or brain stem injury is quite an uncommon presentation. We came across two baffling cases of head trauma in which the patients developed simultaneous bilateral lower motor FNPs without any significant findings in initial brain scans which would suggest the pathophysiology for such a condition. Both the cases were found to be having longitudinal fractures of the temporal bone leading to injury of the facial nerves bilaterally. After conservative management, both the cases showed appreciable neurological improvement on follow-up. Hence, although bilateral FNP can be a diagnostic dilemma, it is quite possible to precisely localize the site of injury and successfully treat it.
Keywords: bilateral facial nerve palsy; temporal bone fracture; House and Brackmann